Bachelor of Science in Nursing; Open & Distance Learning Research Supervision Preparedness: Tutor Perception - Mutowo, Jesca; Chitura, Miriam (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Research Supervision is a process that assists the student to become an independent professional researcher andscholar. In order for that mandate to be met, open and distance (ODL) learning student research supervisorsneed to have appropriate skills to ensure the academic goal of the University of preparing competent researchersand practitioners is reached. This study sought to establish tutor perceptions on ODL research supervisionpreparedness. The researchers used a case study for the qualitative methodology. Purposive sampling methodwas used to select participants from part time tutors who were conducting weekend tutorials. Face to faceinterviews were conducted using structured interview guides. Generated data was organized into differentthemes. Common patterns were grouped into significant themes namely: tutor previous experience, trainingreceived and methods of supervision. The major findings were that, most part time tutors were not inducted intoopen and distance learning research supervision and tutors were relying on the experiences gained during theirown research studies. This resulted in different formats of the research projects being presented by the ODLstudents. Although tutors had access to internet facilities and would prefer supervising students on-line, thetutors did not know how to factor in comments for corrections. The study therefore, recommends an ODLresearch supervision induction/training workshop for tutors. To ensure quality of the final project, a researchsupervision guideline should be established to guide the tutors and students.